FIGURE 7. A–C in Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean - TAVARES, MARCOS; MENDONÇA, JOEL BRAGA DE JR. (Zenodo, 2022)
FIGURE 7. A–C, Moreiradromia antillensis (Stimpson, 1858), scanning electron micrographs. A–C, Female, cw 8.8 mm (MZUSP 5905). Note in (A) very pilose carapace and appendages, which help the crab to hold sponges and other materials firmly against the dorsal body surface. B, Detail of the antennule and antenna. C, Detail of the first article of antenna much wider than long, beaked medially. Scales: A, 1 mm. B, 0.5 mm. C, 0.1 mm. Published as part of TAVARES, MARCOS & MENDONÇA, JOEL BRAGA DE JR., 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 (1) on page 17, DOI:10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155